Prevalence and antimicrobial susceptibility pattern of Klebsiella pneumoniae isolated from various clinical specimens at the University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia - Minichil Worku; Solomon Belay; Tigist Molla; Melak Aynalem; Muluneh Assefa (BMC Infectious Diseases, 2024)
Abstract Background K. pneumoniae become multidrug-resistant (MDR) and commonly poses a serious health threat to patients due to limited therapeutic options. As a result, determining the prevalence and antimicrobial susceptibility patterns of K. pneumoniae isolates from clinical specimens is substantial to patient diagnosis and treatment. Methods and materials A retrospective cross-sectional study was conducted from July 2021 to July 2022 at the University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia. Sociodemographic and laboratory data were collected from registered books using a data collection sheet. All types of samples were collected and processed using standard procedures. Identification of K. pneumoniae was done using Gram stain, colony characterization on culture media, anda series of biochemical tests. Antimicrobial susceptibility testing was done by the Kirby Bauer disc diffusion technique. The data were entered using Epi-info version 7 and exported to SPSS version 20 for analysis. Results Among 2600 clinical specimens, 735 (28.3%) were positive for bacteria, and K. pneumoniae isolates accounted for 147 (20%). Most of them were isolated from neonates and mainly obtained from blood specimens (81.6%). These isolates were 100% resistant to Nalidixic acid, Cefotaxime, and Cefazolin. About 84% and 83.3% of the isolates were also resistant to Ceftriaxone and Tetracycline, respectively. However, they are sensitive to Nitrofurantoin (86.6%), Imipenem (85.7%), Meropenem (79%), and Amikacin (78.3%). The overall proportion of MDR K. pneumoniae isolates accounted for 57.1%. Conclusion The magnitude of MDR K. pneumoniae was very alarming. Therefore, strengthening antimicrobial stewardship programs and antimicrobial surveillance practices is strongly recommended in the study area.